IMPROVING THE STUDENTS’ READING COMPREHENSION THROUGH KNOW-WANT-LEARN STRATEGY - Muhammad Hassan (LPPM STKIP AL MAKSUM, 2022)
Improving The Students’ Reading Comprehension through Know-Want-Learn Strategy atthe first grade students of SMA Negeri 1 Stabat. The objective of this research wasintended to explain the improvement of the students’ interpretative and literal readingcomprehension through Know-Want-Learn Strategy at the first grade students of SMANegeri 1 Stabat especially in class X 3. The strategy of this research was a ClassroomAction Research (CAR) consisted of two cycles, one cycle consisted of four meetings. Itmeans that there were eight meetings for two cycles. This classroom action research wasdone at the first grade students of SMA Negeri 1 Stabat in Langkat regency for Englishsubject. As subject in this research was class X 3 in 2022-2023academic year withstudents’ number as about 32 students. Those consist of 22 women and 10 men. Theinstrument of this research were observation sheet and reading test or evaluation. Thefindings of the research were students achievement in reading comprehension was 54,07in D-test, then Cycle I is 69,07 and it became 73,81 in Cycle II. The students activeness inlearning reading comprehension in the first meeting of Cycle I was 45,39% then itbecame 90,78% in fourth meeting of Cycle II.